The role and place of bioimpedance analysis assessment of body composition of children and adolescents with different body mass - Ya. V. Girsh; O. A. Gerasimchik (Бюллетень сибирской медицины, 2018)
The steady rise of obesity in children and adolescents emphasizes the need for new, integrated approaches to its diagnosis and therapy. When diagnosing obesity and choosing methods for its correction, it is fundamentally important to use reliable methods of estimating the amount of adipose tissue. Using the body mass index is not always sufficient, since it does not provide complete information on quantitative content in the body weight of the patient’s body. For these purposes in clinical medicine use of bioimpedance analysis to assess the indicators, which characterize the basal metabolism, active cell mass, fat and basirova mass and total water content in the body. However, the holding of bioimpedance body composition analysis is currently limited mainly to dietetics and sports medicine, and adult patients. Quite interesting is the use of the bioimpedance method in the pediatric age group for accurate evaluation of body composition of children of various ages and body weight that will allow for dynamic control of all types of metabolism to evaluate the effectiveness of the observation and treatment of patients with overweight and obesity.